The milk of amnesia - Janess, Danielle, 1978- (Hugh MacLennan poetry series., 2021)
"Danielle Janess's debut poetry collection resists the erasing effects of war, nationalism, and forced migration. Following the speaker's arduous relocation to a twenty-first-century Europe still etched with the wounds of the past, the poems take on daring forms and language, becoming theatre, film clips, photographs, and dance, all embodied by a cast of characters marked by the violence of the last century. Arrested in Warsaw within the first twenty days of the Second World War, Janess's maternal grandfather was sent to a Soviet gulag where he survived for three years before joining the Free Polish Army in Russia and later the battle of Monte Cassino in the Italian Campaign. Many of the poems in Milk of Amnesia grow from the soil of Warsaw and Berlin, where the poet-speaker catapults herself and her young child in an effort to locate and unearth their family inheritance. Drawing from the tradition of poetry of witness, Milk of Amnesia performs a visionary resistance, lit with signposts in a charged atmosphere. An address to our ongoing struggles with historical memory, these poems act as both artifact of and antidote to our time."--